Imagem sócio-ambiental do bairro de Cidade Nova, Natal-RN, por seus moradores - Góes, Rachel Medeiros de (2011)
This dissertation investigates how the neighborhood of Cidade Nova, located in the western side of the of Natal, is perceived by its residents in order to understand its socio-environmental image, intending to contribute both to define strategies of urban intervention and environmental education in the area and to consolidate a methodology that addresses this kind of problem. The completion of field research used a multimethod strategy to study the socio-environmental image of urban areas. It consists of: (a) review of local history from literature research, data recorded by the City Hall, news published on the city's newspapers and interviews with former inhabitants, (b) application of questionnaires to inhabitants including emotions, visual perception, memory and local social activities, (c) development of a drawing of the district, (d) conducting focus groups with inhabitants, using as a starting point the results obtained in the previous activities. In steps "b" and "c" attended 32 neighborhood residents, 16 of them being Community Health Workers and other 16 persons appointed by them. In step "d" 10 individuals took part, divided into two groups. The result of the research showed a picture of residents coincident with the image conveyed by the media in relation to the issues: violence, garbage, public policy/social support and appreciation of the beauties of environmental (dunes and Parque da Cidade park). Although Cidade Nova has been regarded as a dirty, noisy and dangerous place, most of the participants say they enjoy living on the neighborhood. Overall, the results corroborate and gain theoretical explanations, as they are interrelated. The socio-environmental image is expressed for instance in the elements dunes, dump, railroad tracks and Central Avenue that gain symbolic connotation influenced by time and socio-economic context. The insecurity and other negative characteristics assigned by the inhabitants and the media are parallel to the place attachment, since the environmental legibility, the time/familiarity and territoriality offer inhabitants the preference for place of residence, setting up their social identity.